Jesus profeta na dinâmica narrativa do terceiro evangelho. - Silva, Leila Janaína Pereira da (2022)
The history of Israel as a people chosen by God was deeply marked by the prophetic movement. This people, throughout its formation process and its relationship with IHWH, will have in the figure of the prophets very significant characters as those who, having received a mission from God, speak in His name. Those who help the people to maintain faith and hope in the God who had once saved them from slavery in Egypt and with whom they had made an Alliance. Regarding Jesus of Nazareth, in all the Gospels there is a clear reference to him as a prophet, even if not in a more detailed and deep way. But, it is possible to notice that in the third Gospel, among the models used by Luke to describe and present to his community, the person of Jesus, his life and his mission project, there is the model of a prophet. Therefore, we ask ourselves: what does the narrative dynamic of the third Gospel reveal about Jesus the prophet? This research aims to reflect on Jesus the prophet in the narrative dynamics of the third Gospel, that is, to reflect on his own way of being a prophet and how to act prophetically. The methodology used in this work consisted of the analysis of the third Gospel as the main source of the study and in bibliographical research. It began by identifying and contextualizing the prophet Jesus in the third Gospel, and for this identification, the narratives that expressly carry the word "Prophet" attributed to Jesus were taken, whether implicitly or explicitly, in narratives coming from the primary source (Mark) or from Lucan itself. Then, we looked at the Lucan way of constructing the prophetic identity of Jesus, giving special attention to the Lucan narratives that more concretely make known the proper way of Jesus to be and to proceed as a prophet. And we end this journey with a reflective presentation, based on the elements provided by the analyzed narratives on the proper way of Jesus the prophet to be and to proceed according to the Lucan narrative dynamics.